Titanium-tantalum alloy surface modification by hydroxyapatite layer on TiO2 nanotubes: Effect on microbial activity - Capellato, Patricia; Vasconcelos, Lucas V.B.; Vilela, Filipe B.; Ribeiro, Gilza Carla; Correia, Cristiane A.P. [UNESP]; Silva, Gilbert; Sachs, Daniela; Rangel, André L.R. [UNESP]; de Cecilia, A.C. Zavaglia; Alves Claro, Ana P.R. [UNESP] (FapUNIFESP (SciELO), 2021)
One of the major health security challenges of the 21st century is the occurrence of microbial infections and bacterial complications that could affect 10 million people by 2050. On the biomaterial field, implant metallic currently replaces partial or total body parts and can fail to be integrated into the body due to infections. This study performs two combined surface modifications on Ti-30Ta alloy, in order to obtain an infection-resistance and osseointegration surface on metallic implants to be tested within bacterial biofilm. The Group 1 investigated surface modifications by the anodization process in the electrolyte glycerol + NH4F 0.25% at 30V- 9 hours and annealed in 530°C (5°C/min). The Group 2 underwent the same process as Group 1 and, additionally, the samples were immersed in 0.3 M CaCl2 and 0.5 M Na2HPO4 solutions for hydroxyapatite growth. The substrate was characterized using scanning electron microscopy (SEM), X-ray diffractometer (XRD) and dynamic contact angle. S. epidermidis bacterial adhesion and biofilm formation. The results indicated that the Group 1 shows a higher antimicrobial activity, hydrophilic behavior and potential to be used for metallic implant applications. The Group 2 with the hydroxyapatite film coating did not have an improvement in the antimicrobial response.
Keywords: Antimicrobial activity; Hydroxyapatite; Nanotubes coating; Surface modification; Titanium alloy